Role of the Gastrografin test in adhesive small bowel obstruction in adults in Senegal - Gueye, Mohamadou L.; Nali, Josua; Toure, Alpha O.; Niasse, Abdou; Faye, Pape M.; Seye, Yacine; Thiam, Ousmane; Seck, Mamadou; Dieng, Madieng (International Surgery Journal, 2026)
Background: Adhesive small bowel obstruction (ASBO) is a common surgical emergency, particularly in low-resource settings where delayed presentation and limited diagnostic resources complicate management. The Gastrografin test may help predict successful conservative treatment. This study evaluated its role in guiding the management of ASBO in adults in Senegal. Methods: A prospective descriptive study with an analytical component was conducted in the Department of General Surgery at Aristide Le Dantec University Hospital in Dakar, Senegal, from December 2015 to December 2021. Adult patients diagnosed with ASBO without clinical or radiological signs of severity were included. All patients underwent a standardized Gastrografin test. The test was considered positive when contrast medium reached the right colon within 24 hours. Clinical outcomes, need for surgical intervention, length of hospital stay, and the diagnostic performance of the test were analyzed. Results: Twenty-seven patients were included (16 men and 11 women), with a mean age of 39.7±17.3 years. Fourteen patients (51.9%) had a positive Gastrografin test, among whom 13 (48.1%) experienced resolution of obstruction without surgery. Fourteen patients (51.9%) required surgery due to a negative test (n=13) or recurrence after initial improvement (n=1). The specificity of the Gastrografin test was 92.9%. Patients with a positive test had a shorter mean hospital stay (4.76 vs. 5.33 days). No mortality occurred. Conclusions: The Gastrografin test is a simple and accessible tool for the management of ASBO. It helps identify patients suitable for conservative treatment while guiding timely surgical intervention.